Sport nutrition knowledge, attitudes, sources of information, and dietary habits of sport-team athletes - Vázquez-Espino, K.; Rodas-Font, G.; Farran-Codina, A. (Nutrients, 2022)
Nutrition knowledge (NK) is one of several factors needed to establish proper eating habits and is especially important for athletes. The aims of this study were the following: to assess the NK of athletes from the Fútbol Club Barcelona; and to study its possible association with self-perceived level of NK, attitude towards nutrition, sources of information, and some dietary habits. We performed a cross-sectional study in two parts. First, we assessed the NK of elite athletes (n = 264) and compared it to the NK of technical teams of different sports (n = 59) and non-athletes (n = 183) of different ages and levels of education. Second, we investigated the associations between NK and other variables. To assess NK, we used a previously validated questionnaire Nutrition Knowledge Questionnaire for Young and Adult Athletes (NUKYA). Athletes showed a low median score (25.1 points), similar to the scores obtained by high school students (19.5) and university Philosophy students (29.0), and significantly lower than the scores of the sports technical team (58.5, p<0.05) and final year students of Human Nutrition and Dietetics (74.6, p<0.05). Moreover, we found statistically significant associations between NK and self-perceived level of NK (n=240,?=0.2546,p=0.0001) intake of fruits and vegetables (n=111,?=0.2701,p=0.0041), and intake of discretionary food (n=111,?=-0.2008,p=0.0001). Athletes with lower scores tended to overestimate their competence in nutrition (Dunning-Kruger effect). We concluded that NK of athletes needs to be improved through education plans that should consider aspects such as the proper selection of information resources and the importance of not consuming supplements without the adequate prescription. Incorporation of technical team and families to the education plan should be considered.